Glyco-STORM: nanoscale mapping of the cellular glycosylation landscape - Schröter, Helene Gregoria; Saß, Steffen; Heilemann, Mike; Kuner, Thomas; Klevanski, Maja (Universität, 2025)
This project utilizes lectin staining combined with multiplexed super-resolution microscopy to explore the glycosylation patterns within different cellular contexts, such as brain tissue, hippocampal neurons, and U2OS cells. This repository contains widefield and super-resolution (dSTORM) data showcasing cellular glycosylation. (2025-03-07)
Gesehen am 17.03.2025
Keywords: Forschungsdaten; Datenbank